The Frequency of Carotid Artery Stenosis in Patients with Ischemic Stroke by Using Color Doppler Ultrasound of Carotid Arteries: Carotid Artery Stenosis in Ischemic Stroke Patients - Begum, Shaheena; Nadeem Ahmed Khan, Muhammad; Jabeen, Sana (Pakistan Journal of Health Sciences, 2022)
Stroke is among leading life threatening neurological emergency and single most important reason for disability. Objective: To determine the frequency of carotid artery stenosis in patients with ischemic stroke by using color Doppler ultrasound of carotid arteries. Method: This Cross sectional study was carried out at Medical Unit-III, Abbasi Shaheed Hospital, and Karachi for Six months from 1st December 2017 to 31st May 2018. 170 diagnosed patients of ischemic stroke fulfilling the inclusion criteria were enrolled. Brief history and bio data were entered in the Pro forma. Ultrasound carotid Doppler was done for all the patients included in the study. Effect modifiers were controlled through stratification of age, gender, hypertension, diabetes mellitus, dyslipidemia, obesity, smoking status and history of CVA to see their effect on the outcome variable. Post stratification chi square test/fisher exact test was applied while odds were computed by binary logistic regression taking p-value of ≤0.05 as significant. Results: Among 170 patients with ischemic stroke visiting Medical Unit-III, Abbasi Shaheed Hospital, Karachi who were included in this study, the mean age of patients was 53.14 ±7.49 years and duration of disease was 2.72±0.89 years. 84 (49.4%) were male and 86 (50.6%) were female. Amongst patients with ischemic stroke, 90 (52.9%) had carotid artery stenosis and 80 (47.1%) did not have carotid artery stenosis. Conclusion: Our study showed that notable number of patients with ischemic stroke had carotid artery stenosis; furthermore, risk factors like hypertension, dyslipidemia and smoking were firmly associated with carotid artery stenosis